2018
DOI: 10.1080/21693277.2018.1509745
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the impact of uncertainty reduction on WLC methods in MTO flow shops

Abstract: With more and more demanding customers, make-to-order (MTO) companies are becoming more important. Workload control (WLC) is specifically developed for MTO companies. Most previous studies have proposed solutions assuming no mismatch between planned and actual production time. However, in real situations, inaccurate estimation of processing time is a daily routine. This study focuses on processing time estimation error and evaluates performance of two different WLC order review and release (ORR) methods throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Due to a stronger spread of Lean Management and the consequent linearization of production flows, we will test our research question in a pure flow shop configuration (Kundu et al, 2018(Kundu et al, , 2019. This means, we consider companies whose production follows a dominant flow sequence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to a stronger spread of Lean Management and the consequent linearization of production flows, we will test our research question in a pure flow shop configuration (Kundu et al, 2018(Kundu et al, , 2019. This means, we consider companies whose production follows a dominant flow sequence.…”
Section: Methodsmentioning
confidence: 99%
“…A production control concept specifically developed for this kind of high variety make-to-order context is Workload Control (WLC). The concept has been shown to significantly improve production systems performances both through simulation (Kundu et al, 2018;Portioli-Staudacher & Tantardini, 2012;Thürer et al, 2012) and, on occasions, in practice. While there are several different approaches to WLC (Bergamaschi et al, 1997;Thürer et al, 2011), a major unifying principle driving WLC is input/output control (I/OC), i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WLC is a PPC mechanism specifically developed for a highvariety, low-volume context. The concept has been shown to significantly improve production system performance through simulation (Kundu et al 2020(Kundu et al , 2018Portioli-Staudacher et al 2020) and, on occasion, in practice.…”
Section: Workload Controlmentioning
confidence: 99%
“…To cope with this challenge, production planning and control (PPC) mechanisms (Małachowski and Korytkowski 2016;Reuter and Brambring 2016) play a fundamental role since PPC is intended to ensure a company's profitability by delivering goods to customers on time and in the right quantities. Workload control (WLC) is a consolidated PPC mechanism that was developed for high-variety, low-volume contexts, such as small-and medium-sized make-to-order (MTO) companies (Kundu et al 2020;Stevenson et al 2005), and it has been demonstrated to provide good margins of improvements (Kundu et al 2020(Kundu et al , 2018Portioli-Staudacher et al 2020). In addition to PPC, to cope with variability and uncertainties-for example, of demand-companies adopt different buffering strategies, such as inventory or capacity buffers (i.e., excess capacity).…”
Section: Introductionmentioning
confidence: 99%